Tripod-shaped Syndactyly in Apert Syndrome with FGFR2 p.P253R Mutation - Chandra Bhan Singh; Biswajit Mishra; Rashmi Patel; Ashok Kumar; Akhtar Ali (Indian Journal of Plastic Surgery)
Apert syndrome is a rare acrocephalosyndactyly (craniosynostosis) syndrome characterized by craniofacial dysmorphism and syndactyly of the hands and feet. It is caused by FGFR2 mutations and inherited in an autosomal dominant manner. This article describes a novel clinical variant of Apert syndrome having bilateral symmetrical tripod-shaped syndactyly in hands with milder craniofacial features in a sporadic case, along with a mutation in the fibroblast growth factor receptor 2 (FGFR2) gene. The patient had shown craniosynostosis, dysmorphic face, ocular hypertelorism, marked depression of the nasal bridge, long philtrum, and low set ears. Direct resequencing of the FGFR2 gene through Sanger’s method identified a heterozygous missense mutation; FGFR2c.758C>G (FGFR2p.P253R) in the exon-7 of the gene.